Distributed memory of neural networks and the problem of the intelligence`s essence - Ibragim E. Suleimenov; Dinara K. Matrassulova; Inabat Moldakhan; Yelizaveta S. Vitulyova; Sherniyaz B. Kabdushev; Akhat S. Bakirov (Institute of Advanced Engineering and Science, 2022)
The question of the nature of the distributed memory of neural networks is considered. Since the memory capacity of a neural network depends on the presence of feedback in its structure this question requires further study. It is shown that the neural networks without feedbacks can be exhaustively described based on analogy with the algorithms of noiseproof coding. For such networks the use of the term